Decadal Changes in the Linkage Between Autumn Sea Ice and the Winter Eurasian Temperature in the 20th Century - Xulong He; Ruonan Zhang; Shuoyi Ding; Qinglong You; Ziyi Cai (Geophysical Research Letters)
Abstract The Warm Arctic‐Cold Eurasia pattern in recent decades has attracted extensive attention and has been partly attributed to rapid sea‐ice loss; however, such a link has been unstable over the past century. Here, we use centennial reanalyzes to investigate the multi‐decadal changes in the linkage between autumn Barents‐Kara sea‐ice and winter Eurasian temperature during the 20th century. Results show a negative Arctic‐Eurasian connection in 1901–1945 (P1), an inconspicuous connection in 1946–1985 (P2), and a significantly positive correlation in 1986–2013 (P3), with distinct stratospheric and tropospheric pathways mechanisms. The contrasting relationships between P1 and P3 are likely due to the different magnitudes of sea‐ice loss and the predominant roles of the atmosphere or sea‐ice in driving different Eurasian temperature effects. As further verification, the best group of Coupled Model Intercomparison Project simulations, which captured the realistic stratospheric pathway in recent decades, can reproduce the historical decadal changes in the Arctic‐Eurasian linkage.